2019
DOI: 10.1007/s12046-019-1154-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-diffusion and diffusion-thermo effects on squeezing flow of unsteady magneto-hydrodynamic Casson fluid between two parallel plates with thermal radiation

Abstract: Present numerical study examines the heat and mass transfer characteristics of unsteady magnetohydrodynamic squeezing flow of Casson fluid between two parallel plates with viscous and Joule dissipation effects in the presence of chemical reaction. The influence of Soret and Dufour parameters on squeezing flow is investigated along with thermal radiation and heat source/sink effects. The heat and mass transfer behaviour of squeezing flow is analysed by considering the rheological Casson fluid model. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…(15). Hence, the present problem is solved with the help of e cient RK-4 technique [51][52][53][54][55][56]. Further, the considered numerical scheme begun by converting the higher order ordinary di erential Eqs.…”
Section: Solution Methodologymentioning
confidence: 99%
“…(15). Hence, the present problem is solved with the help of e cient RK-4 technique [51][52][53][54][55][56]. Further, the considered numerical scheme begun by converting the higher order ordinary di erential Eqs.…”
Section: Solution Methodologymentioning
confidence: 99%
“…Thus, to solve this system of PDE's, we first transformed the system of coupled PDE's to a set of simplified nonlinear ordinary differential equations (ODEs) with the help of the appropriate similarity transformations. Finally, the reduced first order ODEs are solved by using Runge‐Kutta fourth order integration scheme with shooting technique (RK‐SM) 31‐34,42‐51 and the bvp4c matlab function 31‐34,52 . Thus, to achieve the above‐mentioned purpose, the following similarity transformations 9‐14 are suitably used.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Clearly, it is observed that the governing Equations (21) to (23) with conditions Equations (24) to (26) are not amenable to analytical schemes. Hence, in the present paper, an attempt has been made to overcome this difficulty by using RK‐SM 31‐34,42‐51 and bvp4c techniques 31‐34,52 . Thus, before applying the RK‐SM technique, the nonlinear coupled ODE's Equations (21) to (23) are decomposed into a system of first order ODE's and the reduced equations are as follows.…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, once the convergence criteria is reached, the system of ODEs are integrated by using the standard Runge‐Kutta fourth order integration scheme to obtain the desired results. More details can be found in the literature …”
Section: Numerical Solution Proceduresmentioning
confidence: 99%